Arthroscopic Repair of a Lateral Meniscus Oblique Radial Tear - Mark T. Langhans MD, PhD; Mario Hevesi MD, PhD; Xuankang Pan BS; Patrick A. Smith MD; Aaron J. Krych MD (SAGE Publishing, 2024)
Background: Lateral meniscal oblique radial tears (LMORTs) are the most common type of lateral meniscal tears and occur concomitantly with anterior cruciate ligament (ACL) tears in up to 12% of cases. Four types of LMORTs have been classified in the literature based on proximity to the meniscal root and extent of the tear. Type 1 and 2 LMORTs represent partial and complete posterior root tears less than 10 mm from the root insertion. Type 3 and 4 LMORTs are partial and complete posterior radial meniscus tears greater than 10 mm from the root insertion. Indications: Type 3 and 4 LMORTs can and should be addressed with an all-inside side-to-side repair at the time of ACL reconstruction. LMORTs that are not repaired at the time of ACL reconstruction can contribute to persistent instability and meniscal extrusion. Technique Description: Diagnostic arthroscopy is performed to evaluate the posterior aspects of both the medial and lateral meniscus. The medial leaflet is commonly flipped into the notch and scarred to ACL remnant. After identifying and isolating the medial leaflet, an arthroscopic suture passer is used to pass a suture from inferior to superior through the medial leaflet. A second suture is passed from inferior to superior through the lateral leaflet. This is used to shuttle the suture pass through the medial leaflet to the bottom of the meniscus, where it can be tied in a horizontal mattress fashion. The sutures are tied down with aide of an arthroscopic knot pusher. A second set of sutures is passed and used to shuttle a second suture that would be tied posterior to the first suture, again in a horizontal mattress fashion. This allows reduction of the fragments in apposition across the tear. Postoperatively, patients are allowed range of motion from 0° to 90° and to toe touch weightbearing for the first 4 weeks. Patients are advanced to weightbearing as tolerated at 5 weeks. Typical return to sport ranges from 6 to 9 months postoperatively. Results: Results have been published for 2-year outcomes of type 3 and 4 LMORT repairs and have demonstrated persistent improved patient-reported outcomes as well as healing rates that are greater than 80% and in some series approach nearly 100%. Discussion/Conclusion: Arthroscopic all-inside side-to-side surgical repair is a durable and reliable treatment option for patients presenting for ACL reconstruction with concomitant type 3 or 4 LMORT. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.